Dementia and Mental Health During the COVID-19 Pandemic: A Systematic Review - Gaigher, Julia Mariano; Lacerda, Isabel Barbeito; Dourado, Marcia Cristina Nascimento (Frontiers in Psychiatry, 2022)
Objectives: The COVID-19 pandemic brought significant concerns in managing the care of people with dementia, but there are few publications on the mental health of the older adults with dementia and their caregivers during the pandemic compared to studies with other populations. Therefore, this systematic review aims to compare and discuss the impact of the COVID-19 pandemic on people with dementia and their caregivers’ mental health. Methods: A search in PubMed /Medline and ISI electronic databases according to Prisma methodology was performed. We included studies published between 2020 and 2021, with the combination of keywords: “COVID-19 and Mental Health and elderly”, “COVID-19 and mental health and dementia”, “COVID-19 and dementia and caregivers”, “Pandemic and mental health and elderly”, “Pandemic and anxiety”. Results: Twenty-two studies were included. Technology has been an essential ally during the pandemic as all evaluated studies performed data collection remotely. Almost all studies were unanimous in emphasizing that social isolation and detachment can lead to the emergence or increase of neuropsychiatric symptoms and motor dificulties causing new psychiatric symptoms or exacerbating existing ones. However, mixed results were found regarding the impact of the pandemic in people with dementia cognitive functioning. Caregivers have also suffered from the impact of the pandemic, having an increase in the burden of care and emergence of symptoms of stress, depression and anxiety. Few studies suggested measures to alleviate the difficulties of people with dementia and their caregivers. There are reports of the benefits of technology for communication and treatment through teleconsultations, however, not everyone has access to it, making it difficult to disseminate this tool to the target population. Conclusions: In general, studies showed that social isolation can increase deficits in cognition and neuropsychiatric symptoms and caregivers’ burden and anxiety. Therefore, for not intensifying physical and psychological suffering, new ways of care and intervention are needed for the older adults with cognitive deficits and their caregivers. Technological initiatives and support should consider both people with cognitive impairment as well as different technology literacy levels.